Analisis Filsafat Ekonomi Islam terhadap Diskon Dompet Digital: Telaah Kritis Pemikiran Erwandi Tarmizi tentang Potensi Riba dalam Fintech Syariah - Pratama Harista, Redo; Lutfi, Ahmad; Iska, Syukri (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2025)
This study aims to critically examine Erwandi Tarmizi’s perspective on the legal status of digital wallet discounts within the framework of Islamic economic philosophy and the maqāṣid al-sharī‘ah approach. The rapid growth of electronic payment systems in Indonesia, with national electronic money transactions reaching IDR 519.24 trillion in 2023, has intensified scholarly debates regarding the permissibility of promotional incentives such as discounts and cashback, particularly in relation to the potential presence of hidden usury in modern fintech mechanisms. Erwandi asserts that digital wallet discounts constitute benefits derived from a qardh (loan) contract and therefore fall under the category of riba. In contrast, the National Sharia Council of Indonesia (DSN-MUI) through Fatwa No. 116/DSN-MUI/IX/2017, along with contemporary scholars such as Oni Sahroni, argue that digital wallet transactions operate under wadī‘ah or wakālah contracts, positioning discounts as permissible promotional hibah rather than prohibited loan-based gains. Using a library research design combined with a normative-philosophical and contextual approach, this study compares the epistemological foundations and legal implications of these differing viewpoints and analyzes their relevance within the socio-economic realities of the digital economy. The findings reveal that the legal judgment regarding digital wallet discounts cannot be generalized but must be determined based on the structure of the underlying contract, the causal relationship of the benefit, and its impact on public interest. The study concludes that a maqāṣid-based moderation approach is essential for formulating balanced and adaptive regulatory frameworks for Islamic fintech in contemporary economic development.